Brown fat-associated postprandial thermogenesis in humans: Different effects of isocaloric meals rich in carbohydrate, fat, and protein - Aita, Sayuri; Matsushita, Mami; Yoneshiro, Takeshi; Hatano, Takuya; Kameya, Toshimitsu; Ohkubo, Iwao; Saito, Masayuki (Frontiers in Nutrition, 2022)
The increase of whole-body energy expenditure seen after a single meal ingestion, referred to as diet-induced thermogenesis (DIT), substantially varies depending on the meal’s macronutrient composition. Brown adipose tissue (BAT), a site of nonshivering thermogenesis, was reported to be involved in DIT. To examine the effects of meal composition on BAT-associated DIT in humans, healthy male participants underwent [18F]fluorodeoxyglucose–positron emission tomography to assess BAT activity, and respiratory gas analysis for 2 hours after ingestion of a carbohydrate-, protein-, or fat-rich meal (C-meal, P-meal, and F-meal, respectively). The calculated DIT at 2 hours was 6.44 ± 2.01%, 3.49 ± 2.00%, and 2.32 ± 0.90% of the ingested energy after the P-meal, C-meal, and F-meal, respectively. The DIT after C-meal ingestion correlated positively with BAT activity (P = 0.011), and was approximately twice greater in the group with high-BAT activity than in the group with low-BAT activity (4.35 ± 1.74% vs. 2.12 ± 1.76%, P < 0.035). Conversely, the DIT after F-meal or P-meal ingestion did not correlate with BAT activity, with no difference between the two groups. Thus, BAT has a significant role in DIT after ingestion of a carbohydrate-rich meal, but hardly after ingestion either protein- or fat-rich meal.